Sea Lice ( Lepeophtheirus salmonis ) Harbour Putative Fish Pathogens: Insights From Illumina and Nanopore Sequencing - B. Klimesova; N. M. Ruane; R. Domingo‐Bretón; F. Moroni; F. Naya‐Català; J. Pérez‐Sánchez; K. O'Dwyer; O. Lyashevska; H. Rodger; A. Talbot (Journal of Fish Diseases, 2026)
Ectoparasites that penetrate host skin can act as biological or mechanical vectors for pathogens and, in some cases, serve as reservoirs. Crustacean ectoparasites of fish are potential vectors of pathogens, which is especially relevant for obligate pathogens (e.g., Aeromonas salmonicida ) with limited seawater survival. Sea lice ( Lepeophtheirus salmonis ), affecting Atlantic salmon, cause dermal damage and can facilitate secondary infections, resulting in economic losses. While the physical impact of sea lice is well known, their role in pathogen transmission is less clear. The gut bacterial microbiome of lice collected over four months from a salmon farm in Ireland was analysed using Illumina MiSeq and Oxford Nanopore Technologies (ONT) PromethION sequencing for comparison. Illumina and Nanopore sequencing identified 15 and 24 genera of known fish pathogens, respectively. Moreover, Nanopore data revealed up to 15 putative pathogenic species, including Tenacibaculum maritimum , T. dicentrarchi and Vibrio anguillarum , causative agents of tenacibaculosis and vibriosis. The results of this study provide a gut bacterial microbiome characterisation of L. salmonis in a commercial aquaculture setting and demonstrate the potential of sea lice to act as pathogen vectors or reservoirs. These findings have important implications for pathogen surveillance, management, and prevention strategies in salmon aquaculture.

MyLogger: fast logging with HyLogger spectral mineralogy - J. M. Stromberg; C. Laukamp; E. J. Hill; A. Rodger (Australian Journal of Earth Sciences, 2026)

Preserving the gut microbiome: hydrogel-forming microneedle delivery of tetracycline reduces gut microbiome disruption compared to oral administration - Stephen A. Kelly; Li Zhao; Jonathan Nzakizwanayo; Aoife M. Rodgers; Thomas P. Thompson; Andrew J. Lee; Helen O. McCarthy; John W. McGrath; Rebecca J. Ingram; Brian V. Jones; Brendan F. Gilmore; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Antibiotics cause significant gut microbiome dysbiosis, particularly when administered orally. This contributes to antimicrobial resistance (AMR) and is associated with myriad health conditions. Novel drug delivery strategies that minimize gut exposure while maintaining therapeutic efficacy are urgently needed. This study aimed to evaluate whether a novel transdermal system could reduce gut microbiome disruption compared to oral delivery. Sprague-Dawley rats received a single tetracycline dose via oral gavage, IV injection, or hydrogel-forming microneedle patch. Faecal samples were collected longitudinally and analysed using 16 S rRNA gene sequencing. Oral tetracycline caused the greatest disruption to gut microbiota. Compared to the timepoint immediately prior to treatment (Day 5a), peak dysbiosis was observed at Day 7. The Firmicutes: Bacteroidetes ratio was significantly reduced following oral and IV tetracycline therapy, but not following microneedle administration. The most significant reductions in alpha and beta diversity at Day 7 were observed in the oral group. Differential abundance analysis showed oral treatment resulted in the highest number of depleted and enriched taxa. The microbiome-sparing effect of microneedle delivery was consistent across all analytical measures, offering a promising strategy to preserve host microbiome health. This minimally invasive approach represents a clinically viable alternative to oral and IV antibiotic administration.

Evaluating the evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards - Jason J. Kolbe; Jacob D. Ward; C. Mike Norris; John Rodgers; Sydney Wayne; Daniel A. Warner (Evolutionary Ecology, 2026)
Whether phenotypic plasticity facilitates adaptive evolution is a key question in evolutionary ecology. The discovery of limb-length plasticity in two Anolis lizard species led to hypotheses about its role in the Anolis radiation. Yet, whether limb plasticity is realized in nature and has adaptive significance is poorly understood. In this study, we combined a limb-length plasticity experiment, lab-based assays of hatchling behavior, and field-based measures of individual perch-diameter use of hatchling A. sagrei . We compared our findings to previous lab experiments and field studies to better understand the ecological conditions that might elicit limb plasticity and influence the adaptive potential of limb-length in Anolis lizards. Results from our lab experiment did not support limb-length plasticity. Significant limb-length differences due to plasticity were found in some previous experiments but not others. Intriguingly, repeated observations of individual hatchlings at night revealed consistent use of narrow-diameter perches for an island population. In contrast, individual diurnal perch-diameter use in adult A. sagrei was much less uniform. Little evidence exists for adaptive behavior or performance in hatchlings related to limb length and perch diameters. Several aspects of anole behavior and ecology, such as perch preferences and sleep-site use, influence perch-diameter use. Differences among populations in hindlimb length for Bahamian islands often exceed the average plastic response found in lab experiments. Evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards is currently mixed. A better understanding of how perch-diameter use results in biomechanical and developmental cues that influence limb growth is needed. The lack of clear support from lab and field studies urges caution when hypothesizing about the role of limb-length plasticity in the Anolis radiation.

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Rooting for microbes: Impacts of plant breeding on the Kernza rhizosphere - Hannah R. Rodgers; Urszula Norton; Jay B. Norton; Linda T. A. van Diepen (Plant and Soil, 2025)
Aims Kernza® ( Thinopyrum intermedium) is among the first perennial grain crops ever bred and has the potential to address challenges associated with annual agriculture, in part due to its robust microbial partnerships and soil health benefits. However, breeding programs generally select plants based on aboveground traits such as seed size, resulting in unintended consequences on belowground traits such as root exudation and microbial symbioses. This study aimed to investigate the impact of plant breeding on the rhizosphere environment and microbial community of the novel grain crop Kernza. Methods This study is the first to investigate a crop’s rhizosphere environment across breeding cycles, starting with a wild-type population. We collected rhizosphere soil from Kernza plants across nine cycles of selection for increased yield and harvestability, and analyzed labile organic matter pools, potential enzyme activities, phospholipid fatty acids, and DNA from bacteria and arbuscular mycorrhizal fungi. Results We found that plant breeding altered bacterial and arbuscular mycorrhizal fungal communities in the rhizosphere. Selection also reduced rhizosphere labile organic matter and microbial biomass, but not microbial activity, which instead increased across later breeding cycles. Conclusions Our results suggest that the Kernza breeding program created a less abundant but more active rhizosphere microbial community, potentially due to impacts on plants’ stress tolerance, resource allocation, or resource-use strategies.

Future actions for the ocean acidification research community to support marine industries and coastal communities of Aotearoa New Zealand - Rachel Hale; Lea Muetzel; Jessica Ericson; Joanna Copedo; Vonda Cummings; Norman L. C. Ragg; Christina McGraw; Kim Currie; Kirsten Rodgers; Mary A. Sewell (New Zealand Journal of Marine and Freshwater Research, 2025)
Increasing atmospheric CO 2 emissions are altering the carbonate chemistry of seawater in a process known as ocean acidification (OA). This is a growing issue for marine industries and communities. During the 2023 New Zealand Ocean Acidification Community (NZOAC) Conference, the community undertook a horizon scanning exercise to determine potential future activities and opportunities. Conference participants were sent questions that focussed on topics of importance to the Aotearoa New Zealand and global OA community. Sixteen potential actions were identified. During the conference, participants voted for actions they perceived to be most important to give each an overall priority score. In order, the five top priority actions were to (i) re‐engage with policymakers to ensure OA is included in policies around climate change, oceans, fisheries, and education; (ii) maintain funding for current observation platforms; (iii) focus on solutions during engagement actions; (iv) obtain funding for new OA focused research; and (v) engage more with the public through community/public participatory science. We summarise the activities identified to address these actions and discuss potential ways forward for the NZOAC and wider research community to undertake the required research and provide much needed guidance to underpin OA mitigation and adaptation efforts.

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

The Microbial Trojan Horse and Antimicrobial Resistance: Acanthamoeba as an Environmental Reservoir for Multidrug Resistant Bacteria - Ronnie Mooney; Erin Corbett; Elisa Giammarini; Kiri Rodgers; Carla Donet; Ernest Mui; Arhama T. A. Ansari; Ayush Ransingh; Pradnya S. Vernekar; Harleen K. Walia; Jyoti Sharma; John Connolly; et al. (Environmental Microbiology, 2025)
Antimicrobial resistance (AMR) is shaped by environmental pressures, yet the role of microbial predators such as Acanthamoeba in resistance dynamics remains poorly characterized. In this study, Acanthamoeba ‐associated bacterial communities (AAB) exhibited significantly higher multidrug resistance than sediment‐associated bacterial communities (SAB) in a polluted estuarine system. All isolated amoebae belonged to the T4 genotype, suggesting selection for resilient host organisms. AAB displayed elevated multiple antibiotic resistance (MAR) indices and increased resistance to multiple antibiotic classes, particularly aminoglycosides, macrolides, fluoroquinolones and β‐lactams. Correlation analysis revealed that resistance in AAB, but not SAB, was associated with potentially toxic elements (PTEs) known to influence phagocyte survival, including arsenic, vanadium, and calcium. These elements may select for traits that confer metal and antibiotic resistance. The findings support a model where protists act as selective environments for AMR, favoring bacteria that possess enhanced tolerance mechanisms. This work provides the first direct evidence linking PTE exposure to the intracellular resistome of Acanthamoeba ‐associated bacteria. It underscores the need for AMR monitoring frameworks that include protist‐bacteria interactions, with implications for One Health and environmental risk assessment strategies. Moreover, this approach is scalable for application in low/middle‐income countries, where AMR burden is greatest and surveillance capacity remains limited.

The best of both worlds: Why antipredator traits are lost in predator-free havens and how to keep them - Natasha R. LeBas; Jennifer Rodger; Rowan A. Lymbery; Joseph L. Tomkins; Dominique Blache (Biological Conservation, 2025)

Low-damage performance of rocking column bases with Belleville Springs for enhanced seismic resilience - Jiang-Yue Xie; Zhenduo Yan; Junrong Liu; Rui Zhang; Ping Xiang; Xianzhong Zhao; Gregory A. MacRae; G. Charles Clifton; Rajesh P. Dhakal; Shahab Ramhormozian; Geoffrey Rodgers; Pierre Quenneville; et al. (Engineering Structures, 2025)

Determinants of riverine migration success by Atlantic salmon ( Salmo salar ) smolts from rivers across the UK and Ireland - Jessica R. Rodger; Jemma Guthrie; Hannele M. Honkanen; Angus J. Lothian; Jessie Lilly; Marcus Walters; Richie Miller; Lorraine Hawkins; Al Reeve; Jamie Ribbens; Jim Henderson; Debbie Parke; et al. (Journal of Fish Biology, 2025)
There is some evidence that the river migration success of Atlantic salmon smolts, on their first migration to sea, varies both spatially and temporally. However, we have only a poor understanding of what may be driving this variation. In this study, we used acoustic telemetry to quantify the spatial and temporal variations in river migration success in Atlantic salmon smolts on their first migration to sea. In total 4120 Atlantic salmon smolts migrating through 22 rivers in Scotland, England, Ireland, and Northern Ireland over multiple years were included in the study. Individuals were defined as successful migrants if detected leaving the river to enter marine waters. The results show significant temporal (up to 4 years) and spatial (river) variations in migration success, with overall between‐river migration success varying from 3.4% to 97.0% and between years from 3.4% and 61.0%. Temporal variation in migration success was river specific, with some rivers being more temporally stable (exhibiting little variation between years) than others. Across all rivers and years, individual migration success was predicted positively by body condition and negatively by tag burden. The rate of migration success for a population (migration success standardized to a common river distance [proportion km −1 ]) was predicted by a number of environmental factors. The proportion of river catchment that comprised wetland and woodland positively predicted migration success, whereas the proportion of grassland and peatland in a catchment negatively predicted the rate of migration success. Although the mechanisms through which these effects may be operating were not directly examined in this study, we discuss some potential routes through which they may occur.

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Complex landscape, instream and anthropogenic environmental features drive genetic and morphological structuring amongst brown trout (Salmo trutta) populations in a dendritic river system - Jessica R. Rodger; Hannele M. Honkanen; Caroline R. Bradley; Patrick Boylan; Paulo A. Prodöhl; Colin E. Adams (Evolutionary Ecology, 2025)
Untangling the patterns and proximate drivers of intraspecific genetic and phenotypic structuring informs our understanding of the evolutionary processes shaping diversity. This study investigated morphological and genetic structuring of brown trout ( Salmo trutta L.) populations across varying spatial scales in a single, complex, dendritic river catchment and examined the potential natural and anthropogenic environmental features driving this structuring. Morphometric and hierarchical genetic structuring analyses of fish from 22 sampling sites in the River Foyle catchment, Ireland (~ 4500km 2 ) identified 19 morphologically distinct groups and 15 genetically distinct populations, separated by river distances ranging from 0.4 km to 188 km. Isolation by Distance was the main factor shaping both genetic and morphological divergence, indicating that strong philopatry is one of the major drivers of the observed population structuring in this system. However, both natural and anthropogenic environmental variables also explained pairwise genetic and morphological differences between sampling sites. Thus, the pairwise differences in the area of woodland in the upstream catchment, water phosphorus concentration, biological oxygen demand, catchment slope, urban area in upstream catchment, altitude, site specific percentage of canopy cover and dissolved oxygen concentration in the river channel were correlated with genetic divergence. The pairwise differences in the concentration of suspended solids, the extent of bankside overhang, the composition of bedrock, boulder and cobble substrates, watercourse width, catchment slope and site altitude were correlated with between-site morphological differences. We hypothesise that local differential selection pressures comprising both natural environmental variation and variation resulting from anthropogenic effects, in combination with strong philopatry and random genetic processes drive the clearly defined genetic and phenotypic patterns described here.

The effect of downstream translocation on Atlantic salmon Salmo salar smolt outmigration success - Ruaidhri Forrester; Hannele M. Honkanen; Jessie Lilly; Amy Green; Jessica R. Rodger; Brian A. Shields; Philip Ramsden; J. Peter Koene; Melanie Fletcher; Colin W. Bean; Colin E. Adams (Journal of Fish Biology, 2025)
Trap and transport, the capture and subsequent translocation of fish during the freshwater phase of their migration, is becoming more common as a management intervention. Although the technique can be successful, it is costly and can have unintended effects on the fish being transported. This study investigates whether trap and transport can be used to increase the migration success of Atlantic salmon, Salmo salar , smolts in naturally flowing rivers. Seaward‐migrating S. salar ( n = 294) from two UK rivers were tracked using acoustic telemetric techniques. Outmigration success and timing were compared between non‐transported (released at the original in‐river capture site) and transported (released ca. 23 km downstream of the capture site) individuals. Downstream translocation increased the proportion of fish that successfully migrated to marine waters, and there was no indication that transport reduced post‐release survival. The post‐release migration speed of transported fish was slower than expected but this was likely a function of their advanced migration timing rather than an inhibition of their capacity to migrate. These results suggest that trap and transport can increase the outmigration success of S. salar smolts, but the earlier river exit dates of transported fish could negatively affect their survival at sea.

Beat-to-beat blood pressure variability, hippocampal atrophy, and memory impairment in older adults - Trevor Lohman; Isabel Sible; Allison C. Engstrom; Arunima Kapoor; Fatemah Shenasa; Elizabeth Head; Lorena Sordo; John Paul M. Alitin; Aimee Gaubert; Amy Nguyen; Kathleen E. Rodgers; David Bradford; et al. (GeroScience, 2024)
Visit-to-visit blood pressure variability (BPV) predicts age-related hippocampal atrophy, neurodegeneration, and memory decline in older adults. Beat-to-beat BPV may represent a more reliable and efficient tool for prospective risk assessment, but it is unknown whether beat-to-beat BPV is similarly associated with hippocampal neurodegeneration, or with plasma markers of neuroaxonal/neuroglial injury. Independently living older adults without a history of dementia, stroke, or other major neurological disorders were recruited from the community ( N = 104; age = 69.5 ± 6.7 (range 55–89); 63% female). Participants underwent continuous blood pressure monitoring, brain MRI, venipuncture, and cognitive testing over two visits. Hippocampal volumes, plasma neurofilament light, and glial fibrillary acidic protein levels were assessed. Beat-to-beat BPV was quantified as systolic blood pressure average real variability during 7-min of supine continuous blood pressure monitoring. The cross-sectional relationship between beat-to-beat BPV and hippocampal volumes, cognitive domain measures, and plasma biomarkers was assessed using multiple linear regression with adjustment for demographic covariates, vascular risk factors, and average systolic blood pressure. Elevated beat-to-beat BPV was associated with decreased left hippocampal volume ( P = .008), increased plasma concentration of glial fibrillary acidic protein ( P = .006), and decreased memory composite score ( P = .02), independent of age, sex, average systolic blood pressure, total intracranial volume, and vascular risk factor burden. In summary, beat-to-beat BPV is independently associated with decreased left hippocampal volume, increased neuroglial injury, and worse memory ability. Findings are consistent with prior studies examining visit-to-visit BPV and suggest beat-to-beat BPV may be a useful marker of hemodynamic brain injury in older adults.

Is pulmonary inflammation a valid predictor of particle induced lung pathology? The case of amorphous and crystalline silicas - Craig A. Poland; Rodger Duffin; Klaus Weber; Wolfgang Dekant; Paul J.A. Borm (Toxicology Letters, 2024)

Construction and validation of an infant chest phantom for paediatric computed tomography - Seonaid Rodgers; Janette Atkinson; David Cryer; Cameron Storm; Rikki Nezich; Martin A. Ebert; Pejman Rowshanfarzad (Physical and Engineering Sciences in Medicine, 2024)
Paediatric imaging protocols should be carefully optimised to maintain the desired image quality while minimising the delivered patient dose. A paediatric chest phantom was designed, constructed and evaluated to optimise chest CT examinations for infants. The phantom was designed to enable dosimetry and image quality measurements within the anthropomorphic structure. It was constructed using tissue equivalent materials to mimic thoracic structures of infants, aged 0–6 months. The phantom materials were validated across a range of diagnostic tube voltages with resulting CT numbers found equivalent to paediatric tissues observed via a survey of clinical paediatric chest studies. The phantom has been successfully used to measure radiation dose and evaluate various image quality parameters for paediatric specific protocols.

Recovery of multireassortant bluetongue virus serotype 6 sequences from a mule deer (Odocoileus hemionus) and Dorset sheep (Ovis aries) in Colorado - Molly J. Carpenter; Case R. Rodgers; Mia K. Torchetti; Karen A. Fox; Mollie Burton; Tyler J. Sherman; Christie E. Mayo (Veterinary Microbiology, 2024)

A repeated measures cognitive affective bias test in rats: comparison with forced swim test - Benjamin Aliphon; Twain Dai; Jessica Moretti; Marissa Penrose-Menz; Wilhelmina H. A. M. Mulders; Dominique Blache; Jennifer Rodger (Psychopharmacology, 2023)

Food determines ephemerous and non-stable gut microbiome communities in juvenile wild and farmed Mediterranean fish - Tomeu Viver; Alberto Ruiz; Edgar Bertomeu; Martina Martorell-Barceló; Mercedes Urdiain; Amalia Grau; Marco Signaroli; Margarida Barcelo-Serra; Eneko Aspillaga; Aina Pons; Chris Rodgers; Enric Gisbert; et al. (Science of The Total Environment, 2023)

Horse fly and deer fly (Diptera: Tabanidae) species and abundance following logging in northwestern Ontario - Janette Buckley; James A. Schaefer; John L. Ringrose; Marco Raponi; Ian D. Thompson; Philip A. Wiebe; Art R. Rodgers; John M. Fryxell; David V. Beresford (Forest Ecology and Management, 2023)

Lower-ionosphere electron density and effective recombination coefficients from multi-instrument space observations and ground VLF measurements during solar flares - Vida Žigman; Marie Dominique; Davorka Grubor; Craig J. Rodger; Mark A. Clilverd (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Vision-based model updating and evaluation of miter gates on inland waterways - Shuo Wang; Casey Rodgers; Travis Fillmore; Brian Welsh; Thomas Golecki; Shaik Althaf V. Shajihan; Brian A. Eick; Billie F. Spencer (Engineering Structures, 2023)

The effect of a digital health coaching and health education protocol on cognition in adults at-risk for Alzheimer’s - Anthony Campitelli; Joshua L. Gills; Megan D. Jones; Sally Paulson; Jennifer Myers; Kelsey Bryk; Erica N. Madero; Jordan M. Glenn; Charlie H. Rodgers; Jenova A. Kempkes; Michelle Gray (GeroScience, 2023)
Several modifiable lifestyle factors have been linked to cognitive ability and the risk of developing Alzheimer’s disease and related dementias (ADRD). Health coaching (HC) is an intervention that addresses lifestyle factors associated with cognition. The effectiveness of an HC protocol was evaluated and compared with a health education (HE) intervention, representing the current standard of care, in a sample of 216 adults between the ages of 45 and 75 years who were at-risk for developing ADRD. Outcomes examined were global cognition, neuropsychological cognition, and Alzheimer’s risk. HC participants received personalized coaching from a health coach focusing on nutrition, physical activity, sleep, stress, social engagement, and cognitive activity. HE participants received biweekly education materials focusing on the same modifiable lifestyle factors addressed by HC. Participants were assessed at baseline and again 4 months later. Self-reported global cognition scores improved only in the HC group (16.18 to 15.52, p = .03) and neuropsychological cognitive ability improved in the HE group (104.48 to 108.76, p < .001). When non-adherence in the HC group was accounted for, however, the mean change in neuropsychological score was similar between groups ( p > .05), self-reported global cognition demonstrated an even larger mean improvement in the HC group (16.20 to 15.41, p = .01), and the HC group saw an improvement in ADRD protective risk score (− 10.39 to − 11.45, p = .007). These results indicate that HC and HE can both improve cognition, but HC may be more effective and may yield increased protection against ADRD risk.

Seasonal changes in abundance and feeding ecology of an endemic, keystone predator following the introduction of large rainbow trout Oncorhynchus mykiss - Anthony W. Rodger; Trevor A. Starks (Fisheries Management and Ecology, 2022)
Despite documented negative effects on aquatic ecosystems, management agencies commonly receive requests to stock non‐native rainbow trout Oncorhynchus mykiss (Walbaum). We used a multinomial N‐mixture model and a suite of diet analyses to evaluate effects of large (265–530 mm) rainbow trout on reach‐scale abundance and feeding ecology of an important endemic, keystone species, Neosho bass Micropterus velox (Hubbs and Bailey) . We evaluated potential changes by seasonally sampling multiple reaches of an Ozark Highlands stream before and after the introduction of 10,800 rainbow trout. Results suggest that rainbow trout altered the distribution of Neosho bass, as indicated by a negative relationship between rainbow trout density and Neosho bass abundance. Trophically, rainbow trout and Neosho bass

Benefits of a plant-based diet and considerations for the athlete - Keely A. Shaw; Gordon A. Zello; Carol D. Rodgers; Thomas D. Warkentin; Angela R. Baerwald; Philip D. Chilibeck (European Journal of Applied Physiology, 2022)

Biological Sound Sources Drive Soundscape Characteristics of Two Australian Marine Parks - Jessica A. McCordic; Annamaria I. DeAngelis; Logan R. Kline; Candace McBride; Giverny G. Rodgers; Timothy J. Rowell; Jeremy Smith; Jenni A. Stanley; Allison Stokoe; Sofie M. Van Parijs (Frontiers in Marine Science, 2021)
Soundscapes represent an intrinsic aspect of a habitat which, particularly in protected areas, should be monitored and managed to mitigate human impacts. Soundscape ecology characterizes acoustic interactions within an environment, integrating biological, anthropogenic, climatological, and geological sound sources. Monitoring soundscapes in marine protected areas is particularly important due to the reliance of many marine species on sound for biological functions, including communication and reproduction. In this study we establish a baseline understanding of underwater soundscapes within two marine National Park Zones (NPZs) along the east coast of Australia: Cod Grounds Marine Park and an NPZ surrounding Pimpernel Rock within Solitary Islands Marine Park. In each of the NPZs, underwater recorders were deployed twice during the austral winter (33–35 days, 2018 and 60–69 days, 2019) and once during the austral summer (35–71 days, 2018–2019). We used the resulting acoustic recordings to determine hourly presence of anthropogenic and biological sounds between 20 Hz and 24 kHz and analyze their contributions to patterns of received sound levels. Sounds from vessels were recorded on most days throughout monitoring but were not found to influence long-term patterns of sound levels over their corresponding frequencies. Biological sources included dolphins, snapping shrimp, fish choruses, humpback whales, and dwarf minke whales. Dolphins, snapping shrimp, and fish choruses were present in all deployments. Median ambient sound levels showed a consistent diel pattern with increased levels resulting from crepuscular fish choruses combined with a higher intensity of snapping shrimp snaps during those times. Singing humpback whales strongly influenced the overall sound levels throughout the winter migration, while dwarf minke whales were consistently detected in the 2019 winter deployment but were only present in 2 h among the earlier deployments. Patterns of acoustic spectra were similar between the two NPZs, and patterns of soundscape measurements were observed to be driven by seasonal differences in biological contributions rather than anthropogenic sound sources, indicating that these NPZs are not yet heavily impacted by anthropogenic noise. These baseline measurements will prove invaluable in long-term monitoring of the biological health of NPZs.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Translating a Global Emission-Reduction Framework for Subnational Climate Action: A Case Study from the State of Georgia - Marilyn A. Brown; Blair Beasley; Fikret Atalay; Kim M. Cobb; Puneet Dwiveldi; Jeffrey Hubbs; David M. Iwaniek; Sudhagar Mani; Daniel Matisoff; Jaqueline E. Mohan; Jeffrey Mullen; Michael Oxman; et al. (Environmental Management, 2021)
Subnational entities are recognizing the need to systematically examine options for reducing their carbon footprints. However, few robust and comprehensive analyses are available that lay out how US states and regions can most effectively contribute. This paper describes an approach developed for Georgia—a state in the southeastern United States called “Drawdown Georgia”, our research involves (1) understanding Georgia’s baseline carbon footprint and trends, (2) identifying the universe of Georgia-specific carbon-reduction solutions that could be impactful by 2030, (3) estimating the greenhouse gas reduction potential of these high-impact 2030 solutions for Georgia, and (4) estimating associated costs and benefits while also considering how the solutions might impact societal priorities, such as economic development opportunities, public health, environmental benefits, and equity. We began by examining the global solutions identified by Project Drawdown. The resulting 20 high-impact 2030 solutions provide a strategy for reducing Georgia’s carbon footprint in the next decade using market-ready technologies and practices and including negative emission solutions. This paper describes our systematic and replicable process and ends with a discussion of its strengths, weaknesses, and planned future research.

Kinematic Rupture Modeling of Ground Motion from the M7 Kumamoto, Japan Earthquake - A. Pitarka; R. Graves; K. Irikura; K. Miyakoshi; A. Rodgers (Pure and Applied Geophysics, 2020)

Spatial and Temporal Changes in Emergent Marsh and Associated Marsh Birds of the Lower Mobile-Tensaw River Delta in Alabama, USA - Scott A. Rush; John Rodgers; Eric C. Soehren; John A. Trent (Wetlands, 2019)

Current Opinions and Consensus for Studying Tremor in Animal Models - Sheng-Han Kuo; Elan D. Louis; Phyllis L. Faust; Adrian Handforth; Su-youne Chang; Billur Avlar; Eric J. Lang; Ming-Kai Pan; Lauren N. Miterko; Amanda M. Brown; Roy V. Sillitoe; Collin J. Anderson; et al. (The Cerebellum, 2019)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Low-intensity repetitive transcranial magnetic stimulation over prefrontal cortex in an animal model alters activity in the auditory thalamus but does not affect behavioural measures of tinnitus - Wilhelmina H. A. M. Mulders; K. Leggett; V. Mendis; H. Tarawneh; J. K. Wong; J. Rodger (Experimental Brain Research, 2019)

Comparison of ion channel inhibitor combinations for limiting secondary degeneration following partial optic nerve transection - Lillian M. Toomey; Carole A. Bartlett; Maimuna Majimbi; Gopana Gopalasingam; Jennifer Rodger; Melinda Fitzgerald (Experimental Brain Research, 2019)

Characterization of a large sex determination region in Salix purpurea L. (Salicaceae) - Ran Zhou; David Macaya-Sanz; Eli Rodgers-Melnick; Craig H. Carlson; Fred E. Gouker; Luke M. Evans; Jeremy Schmutz; Jerry W. Jenkins; Juying Yan; Gerald A. Tuskan; Lawrence B. Smart; Stephen P. DiFazio (Molecular Genetics and Genomics, 2018)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Species and Genotype Effects of Bioenergy Crops on Root Production, Carbon and Nitrogen in Temperate Agricultural Soil - Andrew S. Gregory; Jennifer A. J. Dungait; Ian F. Shield; William J. Macalpine; Jennifer Cunniff; Mark Durenkamp; Rodger P. White; Adrian Joynes; Goetz M. Richter (BioEnergy Research, 2018)

The duality of ocean acidification as a resource and a stressor - Sean D. Connell; Zoë A. Doubleday; Nicole R. Foster; Sarah B. Hamlyn; Christopher D. G. Harley; Brian Helmuth; Brendan P. Kelaher; Ivan Nagelkerken; Kirsten L. Rodgers; Gianluca Sarà; Bayden D. Russell (Ecology, 2018)
Ecologically dominant species often define ecosystem states, but as human disturbances intensify, their subordinate counterparts increasingly displace them. We consider the duality of disturbance by examining how environmental drivers can simultaneously act as a stressor to dominant species and as a resource to subordinates. Using a model ecosystem, we demonstrate that CO 2 ‐driven interactions between species can account for such reversals in dominance; i.e., the displacement of dominants (kelp forests) by subordinates (turf algae). We established that CO 2 enrichment had a direct positive effect on productivity of turfs, but a negligible effect on kelp. CO 2 enrichment further suppressed the abundance and feeding rate of the primary grazer of turfs (sea urchins), but had an opposite effect on the minor grazer (gastropods). Thus, boosted production of subordinate producers, exacerbated by a net reduction in its consumption by primary grazers, accounts for community change (i.e., turf displacing kelp). Ecosystem collapse, therefore, is more likely when resource enrichment alters competitive dominance of producers, and consumers fail to compensate. By recognizing such duality in the responses of interacting species to disturbance, which may stabilize or exacerbate change, we can begin to understand how intensifying human disturbances determine whether or not ecosystems undergo phase shifts.

Cold tolerance and invasive potential of the redbay ambrosia beetle (Xyleborus glabratus) in the eastern United States - John P. Formby; John C. Rodgers; Frank H. Koch; Natraj Krishnan; Donald A. Duerr; John J. Riggins (Biological Invasions, 2018)

Oxidative stress is associated with late‐stage amoebic gill disease in farmed Atlantic salmon ( Salmo salar L.) - M Marcos‐López; C Ruiz Espinosa; H D Rodger; I O'Connor; E MacCarthy; M A Esteban (Journal of Fish Diseases, 2018)

Piscirickettsia salmonis infection in cultured lumpfish ( Cyclopterus lumpus L.) - M Marcos‐López; N M Ruane; F Scholz; M Bolton‐Warberg; S O Mitchell; S Murphy O'Sullivan; A Irwin Moore; H D Rodger (Journal of Fish Diseases, 2017)
A Piscirickettsia salmonis infection was diagnosed in lumpfish ( Cyclopterus lumpus L.) juveniles held in a marine research facility on the west coast of Ireland. The main clinical signs and pathology included marked ascites, severe multifocal liver necrosis and severe diffuse inflammation and necrosis of the exocrine pancreas and peri‐pancreatic adipose tissue. Numerous Piscirickettsia ‐like organisms were observed by histopathology in the affected organs, and the bacterial species was characterized by molecular analysis. Sequencing of the partial 16S rDNA gene and internal transcribed spacer region showed the lumpfish sequences to be closely related to previously identified Atlantic salmon ( Salmo salar L.) sequences from Ireland. To the authors’ knowledge, this is the first detection of P. salmonis in lumpfish worldwide. The infection is considered potentially significant in terms of lumpfish health and biosecurity.

Technical pre‐analytical effects on the clinical biochemistry of Atlantic salmon ( Salmo salar L.) - M Braceland; K Houston; A Ashby; C Matthews; H Haining; H Rodger; P D Eckersall (Journal of Fish Diseases, 2017)
Clinical biochemistry has long been utilized in human and veterinary medicine as a vital diagnostic tool, but despite occasional studies showing its usefulness in monitoring health status in Atlantic salmon ( Salmo salar L.), it has not yet been widely utilized within the aquaculture industry. This is due, in part, to a lack of an agreed protocol for collection and processing of blood prior to analysis. Moreover, while the analytical phase of clinical biochemistry is well controlled, there is a growing understanding that technical pre‐analytical variables can influence analyte concentrations or activities. In addition, post‐analytical interpretation of treatment effects is variable in the literature, thus making the true effect of sample treatment hard to evaluate. Therefore, a number of pre‐analytical treatments have been investigated to examine their effect on analyte concentrations and activities. In addition, reference ranges for salmon plasma biochemical analytes have been established to inform veterinary practitioners and the aquaculture industry of the importance of clinical biochemistry in health and disease monitoring. Furthermore, a standardized protocol for blood collection has been proposed.

The epidemiology of pancreas disease in salmonid aquaculture: a summary of the current state of knowledge - M D Jansen; B Bang Jensen; M F McLoughlin; H D Rodger; T Taksdal; H Sindre; D A Graham; A Lillehaug (Journal of Fish Diseases, 2017)
Pancreas disease ( PD ) is a viral disease caused by Salmonid alphavirus ( SAV ) that affects farmed Atlantic salmon ( Salmo salar L.) and rainbow trout ( Oncorhynchus mykiss (Walbaum)) in the seawater phase. Since its first description in Scotland in 1976, a large number of studies have been conducted relating to the disease itself and to factors contributing to agent spread and disease occurrence. This paper summarizes the currently available, scientific information on the epidemiology of PD and its associated mitigation and control measures. Available literature shows infected farmed salmonids to be the main reservoir of SAV . Transmission between seawater sites occurs mainly passively by water currents or actively through human activity coupled with inadequate biosecurity measures. All available information suggests that the current fallowing procedures are adequate to prevent agent survival within the environment through the fallowing period and thus that a repeated disease outbreak at the same site is due to a new agent introduction. There has been no scientific evaluation of currently used on‐site biosecurity measures, and there is limited information on the impact of available mitigation measures and control strategies.

Corynebacterium diphtheriae HmuT: dissecting the roles of conserved residues in heme pocket stabilization - Elizabeth B. Draganova; Seth A. Adrian; Gudrun S. Lukat-Rodgers; Cyrianne S. Keutcha; Michael P. Schmitt; Kenton R. Rodgers; Dabney W. Dixon (JBIC Journal of Biological Inorganic Chemistry, 2016)

Genomic comparison of virulent and non‐virulent S treptococcus agalactiae in fish - C M J Delannoy; R N Zadoks; M Crumlish; D Rodgers; F A Lainson; H W Ferguson; J Turnbull; M C Fontaine (Journal of Fish Diseases, 2016)
Streptococcus agalactiae infections in fish are predominantly caused by beta‐haemolytic strains of clonal complex ( CC ) 7, notably its namesake sequence type ( ST ) 7, or by non‐haemolytic strains of CC 552, including the globally distributed ST 260. In contrast, CC 23, including its namesake ST 23, has been associated with a wide homeothermic and poikilothermic host range, but never with fish. The aim of this study was to determine whether ST 23 is virulent in fish and to identify genomic markers of fish adaptation of S . agalactiae . Intraperitoneal challenge of Nile tilapia, O reochromis niloticus ( L innaeus), showed that ST 260 is lethal at doses down to 10 2 cfu per fish, whereas ST 23 does not cause disease at 10 7 cfu per fish. Comparison of the genome sequence of ST 260 and ST 23 with those of strains derived from fish, cattle and humans revealed the presence of genomic elements that are unique to subpopulations of S . agalactiae that have the ability to infect fish ( CC 7 and CC 552). These loci occurred in clusters exhibiting typical signatures of mobile genetic elements. PCR ‐based screening of a collection of isolates from multiple host species confirmed the association of selected genes with fish‐derived strains. Several fish‐associated genes encode proteins that potentially provide fitness in the aquatic environment.

Lace plant ethylene receptors, AmERS1a and AmERS1c, regulate ethylene-induced programmed cell death during leaf morphogenesis - Gaolathe Rantong; Rodger Evans; Arunika H. L. A. N. Gunawardena (Plant Molecular Biology, 2015)

Erratum to: The chronic effects of an extract of Bacopa monniera (Brahmi) on cognitive function in healthy human subjects - C. Stough; J. Lloyd; J. Clarke; L. A. Downey; C. W. Hutchison; T. Rodgers; P. J. Nathan (Psychopharmacology, 2015)

The effect of impedance to root growth on plant architecture in wheat - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Andrew L. Phillips; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

Canopy interactions and physical stress gradients in subtidal communities - Scott Bennett; Thomas Wernberg; Thibaut de Bettignies; Gary A. Kendrick; Robert J. Anderson; John J. Bolton; Kirsten L. Rodgers; Nick T. Shears; Jean‐Charles Leclerc; Laurent Lévêque; Dominique Davoult; Hartvig C. Christie (Ecology Letters, 2015)
Species interactions are integral drivers of community structure and can change from competitive to facilitative with increasing environmental stress. In subtidal marine ecosystems, however, interactions along physical stress gradients have seldom been tested. We observed seaweed canopy interactions across depth and latitudinal gradients to test whether light and temperature stress structured interaction patterns. We also quantified interspecific and intraspecific interactions among nine subtidal canopy seaweed species across three continents to examine the general nature of interactions in subtidal systems under low consumer pressure. We reveal that positive and neutral interactions are widespread throughout global seaweed communities and the nature of interactions can change from competitive to facilitative with increasing light stress in shallow marine systems. These findings provide support for the stress gradient hypothesis within subtidal seaweed communities and highlight the importance of canopy interactions for the maintenance of subtidal marine habitats experiencing environmental stress.

What Does Low-Intensity rTMS Do to the Cerebellum? - N. Morellini; S. Grehl; A. Tang; J. Rodger; J. Mariani; A. M. Lohof; R. M. Sherrard (The Cerebellum, 2015)

Wheat root growth responses to horizontal stratification of fertiliser in a water-limited environment - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

Trait differences in response to chronic nicotine and nicotine withdrawal in rats - K. Z. Kolokotroni; R. J. Rodgers; A. A. Harrison (Psychopharmacology, 2014)

Metastasis of ovarian cancer is mediated by kallikrein related peptidases - Ying Dong; Daniela Loessner; Helen Irving-Rodgers; Andreas Obermair; James L. Nicklin; Judith A. Clements (Clinical & Experimental Metastasis, 2014)

Quantitative Redox Biology: An Approach to Understand the Role of Reactive Species in Defining the Cellular Redox Environment - Garry R. Buettner; Brett A. Wagner; Victor G. J. Rodgers (Cell Biochemistry and Biophysics, 2013)

Differential characterization of emerging skin diseases of rainbow trout – a standardized approach to capturing disease characteristics and development of case definitions - B Oidtmann; S E LaPatra; D Verner‐Jeffreys; M Pond; E J Peeler; P A Noguera; D W Bruno; S St‐Hilaire; C B Schubiger; K Snekvik; M Crumlish; D M Green; et al. (Journal of Fish Diseases, 2013)
Farmed and wild salmonids are affected by a variety of skin conditions, some of which have significant economic and welfare implications. In many cases, the causes are not well understood, and one example is cold water strawberry disease of rainbow trout, also called red mark syndrome, which has been recorded in the UK since 2003. To date, there are no internationally agreed methods for describing these conditions, which has caused confusion for farmers and health professionals, who are often unclear as to whether they are dealing with a new or a previously described condition. This has resulted, inevitably, in delays to both accurate diagnosis and effective treatment regimes. Here, we provide a standardized methodology for the description of skin conditions of rainbow trout of uncertain aetiology. We demonstrate how the approach can be used to develop case definitions, using coldwater strawberry disease as an example.

A modified Latent Class Model assessment of human papillomavirus-based screening tests for cervical lesions in women with atypical glandular cells: a Gynecologic Oncology Group study - Randy L. Carter; Le Kang; Kathleen M. Darcy; James Kauderer; Shu-Yuan Liao; William H. Rodgers; Joan L. Walker; Heather A. Lankes; S. Terence Dunn; Eric J. Stanbridge (Cancer Causes & Control, 2012)

Geographical distribution of salmonid alphavirus subtypes in marine farmed Atlantic salmon, Salmo salar L., in Scotland and Ireland - D A Graham; E Fringuelli; H M Rowley; D Cockerill; D I Cox; T Turnbull; H Rodger; D Morris; M F Mc Loughlin (Journal of Fish Diseases, 2012)
Sequence data from salmonid alphavirus (SAV) strains obtained from farmed marine Atlantic salmon, Salmo salar L. , over a 20‐year period between 1991 and 2011 was reviewed to examine the geographical distribution of the genetically defined SAV subtypes in twelve regions across Ireland and Scotland. Of 160 different Atlantic salmon SAV strains examined, 62 belonged to subtype 1, 28 to subtype 2, 34 to subtype 4, 35 to subtype 5 and 1 to subtype 6. SAV subtypes 1, 4 and 6 were found in Ireland, while subtypes 1, 2, 4 and 5 were found in Scotland. In the majority of regions, there was a clear clustering of subtypes, with SAV subtype 1 being the dominant subtype in Ireland overall, as well as in Argyll and Bute in Scotland. SAV subtype 2 predominated in the Shetland and Orkney Islands. The emergence in Atlantic salmon of subtype 2 strains typically associated with sleeping disease in rainbow trout in Argyll and Bute, strongly suggesting transmission of infection between these species, was noted for the first time. SAV subtype 4 was the most common subtype found in the southern Western Isles, while SAV subtype 5 predominated in the northern Western Isles and north‐west mainland Scotland. No single strain was dominant on sites in the western Highlands, with a number of sites in this region in particular having more than one subtype detected in different submissions. The significance of these results in relation to aspects of the epidemiology of infection, including transmission, biosecurity and wildlife reservoirs are discussed and knowledge gaps identified.

Detection of Neoparamoeba perurans by duplex quantitative Taqman real‐time PCR in formalin‐fixed, paraffin‐embedded Atlantic salmonid gill tissues - E Fringuelli; A W Gordon; H Rodger; M D Welsh; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative duplex real‐time PCR for the detection of Neoparamoeba perurans and the elongation factor α 1 gene (ELF) of Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), are described. A set of primers and probe was designed to amplify a 139‐bp fragment specific to the N. perurans 18S rRNA gene. The test was shown to be very sensitive, being able to detect as little as 13.4 DNA copies per μL corresponding to 0.15 fg of template DNA. In addition, the reaction that detected N. perurans was found to have a high degree of repeatability and reproducibility, to have a linear dynamic range ( R 2 = 0.999) extending over 5 log 10 dilutions and to have a high efficiency (104%). The assay was applied to DNA samples extracted from 48 formalin‐fixed, paraffin‐embedded (FFPE) salmon gill tissues showing varying degrees of gill histopathology and amoebic gill disease (AGD)‐type histopathology ranging from absent to severe (each scored 0–3). Neoparamoeba perurans DNA was detected in all the blocks where AGD‐type histopathology was diagnosed microscopically and in 43.6% of the blocks showing signs of gill pathology. The association between parasitic load and gill histopathology and AGD‐type histopathology severity was also investigated. This study also describes the development and the application of a second real‐time PCR for the generic detection of Neoparamoeba spp ., Page, 1987. A set of primers and probe conserved among the Neoparamoeba spp. was designed to amplify a 150‐bp fragment within the 18S rRNA gene. Applied to N. perurans‐ negative gill tissues, the method was used to exclude the presence of other Neoparamoeba spp. in those blocks where gill pathology was observed microscopically.

Development of a quantitative real‐time PCR for the detection of Tenacibaculum maritimum and its application to field samples - E Fringuelli; P D Savage; A Gordon; E J Baxter; H D Rodger; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative real‐time PCR for the detection of Tenacibaculum maritimum are described. A set of primers and probe was designed to amplify a 155‐bp fragment specific to the T. maritimum 16S rRNA gene. The test was shown to be very sensitive, able to detect as little as 4.8 DNA copies number μL −1 . In addition, the assay was found to have a high degree of repeatability and reproducibility, with a linear dynamic range ( R 2 = 0.999) extending over 6 log 10 dilutions and a high efficiency (100%). The assay was applied to DNA samples extracted from 48 formalin‐fixed paraffin‐embedded (FFPE) Atlantic salmon, Salmo salar, gill tissues showing varying degrees of gill pathology (scored 0–3) and from 26 jellyfish samples belonging to the species Phialella quadrata and Muggiaea atlantica . For each sample, the bacterial load was normalised against the level of the salmonid elongation factor alpha 1 (ELF) detected by a second real‐time PCR using previously published primers and probe. Tenacibaculum maritimum DNA was detected in 89% of the blocks with no signs of gill disease as well as in 95% of the blocks with mild‐to‐severe gill pathology. Association between bacterial load and gill pathology severity was investigated. T. maritimum DNA was detected at low level in four of the 26 jellyfish tested.

Effect of low-dose acute tryptophan depletion on the specificity of autobiographical memory in healthy subjects with a family history of depression - Hamid A. Alhaj; Matthew Selman; Victoria Jervis; Jacqui Rodgers; Stephen Barton; R. Hamish McAllister-Williams (Psychopharmacology, 2012)

Effects of chronic nicotine, nicotine withdrawal and subsequent nicotine challenges on behavioural inhibition in rats - K. Z. Kolokotroni; R. J. Rodgers; A. A. Harrison (Psychopharmacology, 2012)

Acute nicotine increases both impulsive choice and behavioural disinhibition in rats - Katerina Zoe Kolokotroni; Robert J. Rodgers; Amanda A. Harrison (Psychopharmacology, 2011)

Impacts of climate change on wheat anthesis and fusarium ear blight in the UK - James W. Madgwick; Jon S. West; Rodger P. White; Mikhail A. Semenov; James A. Townsend; Judith A. Turner; Bruce D. L. Fitt (European Journal of Plant Pathology, 2011)

Characterization of basal pseudopod-like processes in ileal and colonic PYY cells - Diego V. Bohórquez; Rashmi Chandra; Leigh Ann Samsa; Steven R. Vigna; Rodger A. Liddle (Journal of Molecular Histology, 2011)

Plasma Membrane Integrity and Survival of Melanoma Cells After Nanosecond Laser Pulses - Francisco G. Pérez-Gutiérrez; Santiago Camacho-López; Rodger Evans; Gabriel Guillén; Benjamin S. Goldschmidt; John A. Viator; Guillermo Aguilar (Annals of Biomedical Engineering, 2010)

Pseudopod-like basal cell processes in intestinal cholecystokinin cells - Rashmi Chandra; Leigh Ann Samsa; Steven R. Vigna; Rodger A. Liddle (Cell and Tissue Research, 2010)

Prospective longitudinal studies of salmonid alphavirus infections on two Atlantic salmon farms in Ireland; evidence for viral persistence - D A Graham; E Fringuelli; C Wilson; H M Rowley; A Brown; H Rodger; M F McLoughlin; C McManus; E Casey; L J McCarthy; N M Ruane (Journal of Fish Diseases, 2010)
Prospective longitudinal studies of two outbreaks of pancreas disease in Atlantic salmon (AS), Salmo salar L., in Ireland were conducted. Both outbreaks occurred during the marine phase of production, with one caused by salmonid alphavirus subtype 1 (SAV1) and the other by SAV4. In addition to screening a range of tissues by real‐time reverse transcriptase polymerase chain reaction (RRT‐PCR), virological, serological and histopathological examinations were performed along with partial genome sequencing and results were related to environmental and production data and farm history. On Farm 1 (marine sampling only), infection was detected within 3 weeks of smolts being placed on the farm, while on Farm 2 (freshwater and marine sampling), infection was first detected 315 days after transfer to sea. In both outbreaks, RRT‐PCR signals were detected in a range of tissues including gill, heart, kidney, pancreas/pyloric caeca, brain and serum. Persistence of signal was longest in gill and heart (≥265 days on both farms) and shortest in serum. Mortalities on the two farms varied from 10.9% to 30%. In both cases, partial genome sequence of the causative viruses were identical to SAV strains detected in previous populations of AS on each of the study farms, including populations with which the study populations overlapped in time and space.

Source mechanisms of the June 2004 Tabuk earthquake sequence, Eastern Red Sea margin, Kingdom of Saudi Arabia - K. S. Aldamegh; K. M. Abou Elenean; H. M. Hussein; A. J. Rodgers (Journal of Seismology, 2009)

Phylogenetic analyses and molecular epidemiology of European salmonid alphaviruses (SAV) based on partial E2 and nsP3 gene nucleotide sequences - E Fringuelli; H M Rowley; J C Wilson; R Hunter; H Rodger; D A Graham (Journal of Fish Diseases, 2008)
Sequence data were generated for portions of the E2 and nsP3 genes of 48 salmonid alphaviruses from farmed Atlantic salmon (AS), Salmo salar L . , and rainbow trout (RT), Oncorhynchus mykiss (Walbaum), in marine and freshwater environments, respectively, from the Republic of Ireland, Northern Ireland, England, Scotland, Norway, France, Italy and Spain between 1991 and 2007. Based on these sequences, and those of six previously published reference strains, phylogenetic trees were constructed using the parsimony method. Trees generated with both gene segments were similar. Clades corresponding to the three previously recognized subtypes were generated and in addition, two further new clades of viruses were identified. A single further strain (F96‐1045) was found to be distinct from all of the other strains in the study. The percentage of nucleotide divergence within clades was generally low (0–4.8% for E2, 0–6.6% for nsP3). Interclade divergence tended to be higher (3.4–19.7% for E2, 6.5–28.1% for nsP3). Based on these results and using current SAV terminology, the two new clades and F96‐1045 were termed SAV subtypes 4, 5 and 6, respectively. SAV4 contained AS strains from Ireland and Scotland, while SAV5 contained only Scottish AS strains. Recently identified SAV strains from RT in Italy and Spain were shown to belong to SAV2. In addition, marine AS strains belonging to SAV2 were identified for the first time. Analysis of the origin of several clusters of strains with identical E2 and nsP3 sequences strongly support horizontal transmission of virus between farms and aquaculture companies. Evidence in support of vertical transmission was not found.

Ocean acidification and calcifying reef organisms: a mesocosm investigation - P. L. Jokiel; K. S. Rodgers; I. B. Kuffner; A. J. Andersson; E. F. Cox; F. T. Mackenzie (Coral Reefs, 2008)

Improving the level of seismic hazard parameters in Saudi Arabia using earthquake location - Abdullah M. Al-Amri; Arthur J. Rodgers; Tariq A. Al-Khalifah (Arabian Journal of Geosciences, 2008)

Grooming, scratching and feeding: role of response competition in acute anorectic response to rimonabant in male rats - A. J. Tallett; J. E. Blundell; R. J. Rodgers (Psychopharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Actin plays a crucial role in the phagocytosis and biological response to respirable quartz particles in macrophages - Petra Haberzettl; Rodger Duffin; Ursula Krämer; Doris Höhr; Roel P. F. Schins; Paul J. A. Borm; Catrin Albrecht (Archives of Toxicology, 2007)

Improving fluorometry as a source tracking method to detect human fecal contamination - Peter G. Hartel; Jennifer L. McDonald; Lisa C. Gentit; Sarah N. J. Hemmings; Karen Rodgers; Katy A. Smith; Carolyn N. Belcher; Robin L. Kuntz; Yaritza Rivera-Torres; Ernesto Otero; Eduardo C. Schröder (Estuaries and Coasts, 2007)

Atypical anxiolytic-like response to naloxone in benzodiazepine-resistant 129S2/SvHsd mice: role of opioid receptor subtypes - R. J. Rodgers; R. Augar; N. Berryman; C. J. Hansom; M. L. O’Mahony; R. M. Palmer; A. Stevens; A. J. Tallett (Psychopharmacology, 2006)

Cellular uptake and cytotoxic potential of respirable bentonite particles with different quartz contents and chemical modifications in human lung fibroblasts - Stefan Geh; Raif Yücel; Rodger Duffin; Catrin Albrecht; Paul J. A. Borm; Lorenz Armbruster; Monika Raulf-Heimsoth; Thomas Brüning; Eik Hoffmann; Albert W. Rettenmeier; Elke Dopp (Archives of Toxicology, 2006)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Longitudinal serological surveys of Atlantic salmon, Salmo salar L., using a rapid immunoperoxidase‐based neutralization assay for salmonid alphavirus - D A Graham; V A Jewhurst; H M Rowley; M F McLoughlin; H Rodger; D Todd (Journal of Fish Diseases, 2005)
Longitudinal serological surveys for salmon pancreas disease virus (SPDV), the causal agent of pancreas disease (PD), were conducted on multiple caged populations of Atlantic salmon, Salmo salar L., on two farms over a 77‐week period (farm 1, freshwater and marine stages) and a 36‐week period (farm 2, marine stage only), using a microtitre‐based virus neutralization (VN) assay. Collected sera were also screened for viraemia with SPDV, and pancreas, heart and muscle tissues were examined for lesions consistent with PD. Outbreaks of PD occurred during the marine phase on both farms, as demonstrated by seroconversion, the isolation of virus and progressive histopathological changes consistent with a PD outbreak. All populations monitored showed a progressive increase in seroprevalence of 90–100%, typically accompanied by rises in geometric mean antibody titres. With the exception of one caged population, which showed a marked biphasic seroprevalence pattern, the seroprevalence figures in the remaining four monitored populations remained high (≥70%) until the end of the study period. Peak VN titres of ≥1/1280 were detected on both farms. The results provide essential baseline information for the interpretation of SPDV VN serology results, and indicate that this methodology is suited to both the diagnosis and seroepidemiology of SPDV infections.

The reality of psychomotor problems, and the possibility of Parkinson?s disorder, in some recreational ecstasy/MDMA users: a rejoinder to Sumnall et al. (2003) - A. C. Parrott; J. Rodgers; T. Buchanan; A. B. Scholey; T. Heffernan; J. Ling (Psychopharmacology, 2004)

Effects of habitat, wave exposure, and marine protected area status on coral reef fish assemblages in the Hawaiian archipelago - A. M. Friedlander; E. K. Brown; P. L. Jokiel; W. R. Smith; K. S. Rodgers (Coral Reefs, 2003)

Algicidal Effectiveness of Clearigate, Cutrine-Plus, and Copper Sulfate and Margins of Safety Associated with Their Use - C. L. Murray-Gulde; J. E. Heatley; A. L. Schwartzman; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 2002)

Seismic Discrimination of the May 11, 1998 Indian Nuclear Test with Short-period Regional Data from Station NIL (Nilore, Pakistan) - A. J. Rodgers; W. R. Walter (Pure and Applied Geophysics, 2002)

Buffer‐Zone Distances to Protect Foraging and Loafing Waterbirds from Disturbance by Personal Watercraft and Outboard‐Powered Boats - James A. Rodgers; Stephen T. Schwikert (Conservation Biology, 2002)
Outdoor recreation and ecotourism can have negative effects on wildlife species, so it is important to determine buffer zones within which activities near critical wildlife areas are limited. We exposed 23 species of waterbirds ( Pelecaniformes, Ciconiiformes, Falconiformes, Charadriiformes) to the direct approach of a personal watercraft ( PWC) and an outboard‐powered boat to determine their flush distances. We used 11 sites with a mixture of low, moderate, and high amounts of human activity along the east and west coasts of Florida during September–November 1998 and April–June 1999. We detected considerable variation in flush distances among individuals within the same species and among species in response to both types of vessels. Average flush distances for the PWC ranged from 19.5 m ( Least Tern [ Sterna antillarum ]) to 49.5 m (Osprey [ Pandion haliaetus ]), whereas average flush distances for the outboard‐powered boat ranged from 23.4 m ( Forster's Tern [ S. forsteri ]) to 57.9 m (Osprey). Larger species generally exhibited greater average flush distances for both types of watercraft. A comparison of the flush distances elicited by each watercraft indicated that only the Great Blue Heron ( Ardea herodias ) exhibited significantly larger flush distances ( t test, p Anhinga anhinga ], Little Blue Heron [ Egretta caerulea ], Willet [ Catoptrophorus semipalmatus ], and Osprey) exhibited significantly larger flush distances ( t test, p t test, p > 0.05) in their flush distances in response to the fast‐moving PWC and the outboard‐powered boat. Our data suggest that a single buffer‐zone distance can be developed for both PWC and outboard‐powered vessels. Buffer zones of 180 m for wading birds, 140 m for terns and gulls, 100 m for plovers and sandpipers, and 150 m for ospreys would minimize their disturbance at foraging and loafing sites in Florida.

Effect of a freeze-dried CMC/PLGA microsphere matrix of rhBMP-2 on bone healing - Jay A. Schrier; Betsy F. Fink; Janet B. Rodgers; Henry C. Vasconez; Patrick P. DeLuca (AAPS PharmSciTech, 2001)

Consequences of Polluted Environments on Population Structure: The Bank Vole (Clethrionomys Glareolus) at Chornobyl - R.J. Baker; A. M. Bickham; M. Bondarkov; S.P. Gaschak; C.W. Matson; B.E. Rodgers; J.K. Wickliffe; R.K. Chesser (Ecotoxicology, 2001)

Integrating Nonindigenous Aquatic Plant Control with Protection of Snail Kite Nests in Florida - JAMES A. RODGERS, JR.; DANIEL D. THAYER; HENRY T. SMITH (Environmental Management, 2001)

Heterogeneity of RMA-S cell line: derivatives of RMA-S cells lacking H2-K b and H2-D b expression - Dewey Howell; Jonathan M. Levitt; Patricia A. Foster; Margaretha M. Guenther; Said M. Shawar; Robert R. Rich; John R. Rodgers (Immunogenetics, 2000)

Mineralogical and textural changes accompanying ageing of silica sinter - N. R. Herdianita; P. R. L. Browne; K. A. Rodgers; K. A. Campbell (Mineralium Deposita, 2000)

Characterization of CHO-K1 cells stably expressing PDE-IV enzymes - D. J. Pon; M. Plant; J. Tkach; L. Boulet; E. Muise; R. A. Allen; I. W. Rodger (Cell Biochemistry and Biophysics, 1998)

Systemic iridovirus infection in freshwater angelfish, Pterophyllum scalare (Lichtenstein) - H.D. Rodger; M. Kobs; A. Macartney; G.N. Frerichs (Journal of Fish Diseases, 1997)

Heavy metal and selenium levels in endangered wood storksMycteria americana from nesting colonies in Florida and Costa Rica - Joanna Burger; James A. Rodgers; Michael Gochfeld (Archives of Environmental Contamination and Toxicology, 1993)

Multiple drug resistance inAerobacter aerogenes - P. G. Bolion; A. C. R. Dean; P. J. Rodgers (Antonie van Leeuwenhoek, 1967)